Hubungan Pendidikan dan Pengetahuan Ibu Tentang Anemia dengan Keteraturan Konsumsi Tablet Darah Wilayah Kerja Puskesmas Penanggalan Provinsi Aceh Tahun 2023 - Fitri Wulandari Sinaga; Ariska Fauzianty; Nova Isabella Mariance Br Napitupulu (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia is one of the public health problems experienced by many pregnant women in Indonesia, including in Aceh Province. One of the efforts to prevent anemia is by consuming iron tablets (TTD) regularly. This study aims to determine the relationship between the level of education and knowledge of mothers about anemia with the regularity of blood tablet consumption. This study used a quantitative approach with a cross-sectional design. The study sample consisted of 100 pregnant women in the Penanggalan Health Center working area, selected through purposive sampling technique. Data were collected using a structured questionnaire and analyzed using the Chi-Square test. The results showed a significant relationship between the level of education (p = 0.032) and knowledge about anemia (p = 0.005) with the regularity of blood tablet consumption. Mothers with higher education and good knowledge tend to be more regular in consuming blood tablets. Improvement of health education is needed through routine counseling to increase mothers' awareness of the importance of preventing anemia during pregnancy.